2010
DOI: 10.2353/ajpath.2010.090521
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Mitochondrial Chaperone TRAP-1 As a Novel Molecular Target in Localized and Metastatic Prostate Cancer

Abstract: Molecular chaperones of the heat shock protein-90 (Hsp90) family promote cell survival, but the molecular requirements of this pathway in tumor progression are not understood. Here, we show that a mitochondria-localized Hsp90 chaperone, tumor necrosis factor receptor-associated protein-1 (TRAP-1), is abundantly and ubiquitously expressed in human high-grade prostatic intraepithelial neoplasia, Gleason grades 3 through 5 prostatic adenocarcinomas, and metastatic prostate cancer, but largely undetectable in norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
111
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 30 publications
9
111
0
2
Order By: Relevance
“…Expression analysis with oligonucleotide microarrays revealed that TRAP1 is one of the target genes elevated by the Myc oncogene (38). TRAP1 was over-expressed in primary human fibroblasts and mouse prostate by SV40-induced malignant transformation (39,40). Various cancer cell lines, including mouse adenocarcinoma, and specimens from human cancer patients also consistently showed over-expression of TRAP1, while it remained undetectable in normal cells and tissues (16,40).…”
Section: Regulation Of Trap1 and Mitochondrial Hsp90mentioning
confidence: 99%
“…Expression analysis with oligonucleotide microarrays revealed that TRAP1 is one of the target genes elevated by the Myc oncogene (38). TRAP1 was over-expressed in primary human fibroblasts and mouse prostate by SV40-induced malignant transformation (39,40). Various cancer cell lines, including mouse adenocarcinoma, and specimens from human cancer patients also consistently showed over-expression of TRAP1, while it remained undetectable in normal cells and tissues (16,40).…”
Section: Regulation Of Trap1 and Mitochondrial Hsp90mentioning
confidence: 99%
“…5 Little is known about TRAP1 signal transduction: the first most important finding on TRAP1 function came from studies by the Altieri's group, which identified TRAP1 as a member of a cytoprotective network selectively active in the mitochondria of tumor tissues. 6 The same group has recently proposed TRAP1 as a novel molecular target in localized and metastatic prostate cancer, 7 and is now involved in a promising preclinical characterization of mitochondria-targeted smallmolecule HSP90 inhibitors. 8,9 Besides some well-characterized TRAP1 functions in mitochondria, during preparation of this manuscript it was reported that interference by HSP90 chaperones triggers an unfolded protein response (UPR) and activates autophagy in the mitochondria of tumor cells.…”
mentioning
confidence: 99%
“…10,11 Loss of cancer suppressor genes localized to chromosome 8p,10q,13q, 16q are sen in early prostatic carcinogenesis.p53 mutation in primary prostate cancer is low and more frequently seen in metastatic carcinoma hence p53 mutation is a late event in prostate cancer. Loss of PTEN gene and KAI gene are also important in prostatic cancer.About 70% of men with prostate cancer lost PTEN gene at the time of diagnosis.Loss of ecadherin and CD44 have also being observed 15 . RUNX2 is a transcription factor that prevents cancer cells undergoing apoptosis and also contribute to development of Prostate carcinoma.…”
Section: Genetic Factorsmentioning
confidence: 97%
“…PTEN gene at the time of diagnosis.Loss of ecadherin and CD44 have also being observed 15 . RUNX2 is a transcription factor that prevents cancer cells undergoing apoptosis and also contribute to development of Prostate carcinoma.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation